The Influence of Students’ Interest in Digital Writing Platforms on Their Writing Achievement in Undergraduate Students - Galuh Uzhma Lailly; Syalwa Noviana Putri; Risma Wahyu Aprilia; Meisha Frida Aurelia; Nadia Citra Khairunissa; Sujito Sujito (Indonesian Journal Publisher, 2026)
This study investigates the influence of undergraduate students’ interest in digital writing platforms on their writing achievement. The research employed a quantitative correlational design involving 35 undergraduate students enrolled in an English writing course at a university in Indonesia. Data were collected through a questionnaire measuring students’ interest in digital writing platforms and a writing test assessed using the ESL Composition Profile rubric. Descriptive statistics and Pearson Product-Moment Correlation analysis were conducted using IBM SPSS Statistics. The findings revealed that most students demonstrated moderate to high levels of interest in digital writing platforms, with 54.3% categorized as having high interest, while only 2.9% showed low interest. Students’ overall writing achievement was classified at a moderate level (M = 67.54, SD = 3.53), with content receiving the highest average score among the five assessed writing components. The correlation analysis indicated a statistically significant negative relationship between students’ interest in digital writing platforms and their writing achievement (r = -0.592, p < 0.05), suggesting that higher levels of interest were associated with lower academic writing performance. These findings imply that although digital writing platforms can enhance students’ engagement, motivation, and accessibility in writing activities, they may also promote informal writing habits that are inconsistent with formal academic writing conventions. Therefore, educators should integrate explicit academic writing instruction, including guidance on grammar, organization, vocabulary, and formal writing conventions, into the use of digital platforms so that students’ digital engagement can effectively support the development of their academic writing proficiency.